High performance polymer solar cells based HfO2 passivated 2D-HfX2 (XS, Se) as a hole transport layers. (1st December 2022) - Huang, Chengwen; Yu, Huangzhong
Abstract: Due to the excellent carrier mobility, higher optical transmission, and suitable work function (WF), two-dimensional (2D) hafnium disulfide (HfS2 ) and hafnium Selenide (HfSe2 ) have enormous potential as charge-transporting layers in polymer solar cells (PSCs). However, there are some deficits in the HfX2 (XS, Se) films, which limits the transmission of charge and improves the recombination of charge in optoelectronic devices. In this work, the HfO2 are formed on HfX2 (XS, Se) surfaces by oxygen plasma treatment to passivate surface defects of HfX2 (XS, Se), which results in the reduction of defects and the increase of conductivity in HfX2 (XS, Se) film. Moreover, the HfO2 induces an interface dipole layer at the HfO2 /HfX2 (XS, Se) interface and forms a p-type doping of HfX2 (XS, Se), which leads to an increase of HfX2 (XS, Se) WF. When the HfX2 /HfO2 (XS, Se) films are used as hole-transporting layers (HTL), the PSCs based on PM6: BTP-eC9: PC71 BM get a higher PCE of 17.76 % (HfS2 /HfO2 ) and 17.83 % (HfSe2 /HfO2 ) respectively, which is superior to those based on PEDOT:PSS HTL. This work shows that the 2D HfX2 (XS, Se) materials have a promising application in the preparation of efficient PSCs. Graphical Abstract: ga1 Highlights: The HfO2 are formed on HfX2 (XS, Se) surfaces to passivate surface defects. The oxygen plasma results in the increase of conductivity in HfX2 (XS, Se) films. The HfO2 leads to an increase of HfX2 (XS, Se) work function. The devices with HfX2 /HfO2 (XS, Se) films get a higher efficiency. Simultaneously, the modified devices show better stability.